2006
DOI: 10.1016/s0828-282x(06)70295-1
|View full text |Cite
|
Sign up to set email alerts
|

Q fever endocarditis: A case report and review of the literature

Abstract: E ndocarditis is the most common presentation of chronic Q fever, a zoonosis caused by the obligate intracellular bacteria Coxiella burnetii. Commonly believed to be a rare disorder, it has been estimated to account for up to 5% of all endocarditis cases worldwide (1-3). It occurs almost exclusively in patients who have pre-existing valvular disease or who are immunocompromised (4). Unlike typical cases of endocarditis, the clinical presentation of chronic Q fever is often nonspecific. Furthermore, specialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Her titers were slow to decrease, but this may be expected within the first 3‐6 months after the acute illness. However, since she did develop mild aortic valve thickening, there was concern for development of endocarditis, since echocardiographic evidence of infection may be absent in Q fever endocarditis . One study showed that TTE revealed abnormalities in only 12% of cases, which is due to the small size and nodular shape of the vegetations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Her titers were slow to decrease, but this may be expected within the first 3‐6 months after the acute illness. However, since she did develop mild aortic valve thickening, there was concern for development of endocarditis, since echocardiographic evidence of infection may be absent in Q fever endocarditis . One study showed that TTE revealed abnormalities in only 12% of cases, which is due to the small size and nodular shape of the vegetations .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Duke criteria for infective endocarditis were revised in 2000 to include a Q fever phase I IgG titer of greater than 1:800 or a single positive blood culture for C burnetti as a major criterion . A phase I IgG titer of greater than 1:800 has been shown to have a specificity of 99.6% for diagnosis of Q fever endocarditis . Our patient's TEE remained inconclusive, and given the high mortality of approximately 37% associated with Q fever endocarditis due to delays in diagnosis and treatment, the benefits of empiric treatment were thought to outweigh the risks .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Q fever endocarditis, blood cultures are usually negative, and transthoracic echocardiogram is not sensitive for demonstrating vegetations. 4 Serology is key to diagnosis, as there is no available routine culture. Usually, an increase in phase 1 IgG antibodies to 1:800 or greater is confirmatory for diagnosis of chronic Q fever endocarditis with a sensitivity of 100% and specificity of 99.6%, although an increase phase 1 IgG antibodies to 1:128 or greater is also supportive.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in phase II IgG antibodies to 1:200 or greater has sensitivity of 81.9% and specificity of 96.1% and phase II IgM to 50 or greater has sensitivity of 67.2% and specificity of 98.8% for diagnosis of active Q fever. 1,2,4,5 Doxycycline and hydroxychloroquine combination has been shown to be effective therapy for Q fever endocarditis. Despite delay in diagnosis and treatment, the patient has done well since the initiation of appropriate therapy.…”
Section: Discussionmentioning
confidence: 99%